2007
DOI: 10.1007/s11325-007-0148-4
|View full text |Cite
|
Sign up to set email alerts
|

Circulating nitric oxide (NO), asymmetric dimethylarginine (ADMA), homocysteine, and oxidative status in obstructive sleep apnea–hypopnea syndrome (OSAHS)

Abstract: Obstructive sleep apnea-hypopnea syndrome (OSAHS) with episodic hypoxia-reoxygenation is associated with increased cardiovascular morbidity and mortality. Therefore, increased homocysteine, asymmetric dimethylarginine (ADMA), oxidative status, and decreased nitric oxide levels have been implicated as possible mechanisms for development of cardiovascular diseases. We aimed to investigate changes in the levels of these substances in patients with OSAHS in comparison with nonapneic controls. Thirty-four OSAHS pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 42 publications
2
25
0
1
Order By: Relevance
“…21,22 Increased plasma concentration of asymmetric dimethylarginine is associated with hypertension, pulmonary hypertension, hypercholesterolemia, and severe peripheral artery occlusive diseases. 15,17,23,24 These findings suggest that asymmetric dimethylarginine is responsible for endothelial dysfunction. Barceló et al 25 assessed plasma asymmetric dimethylarginine in subjects with OSA and found it to be significantly higher in these subjects irrespective of the presence of further cardiovascular risk.…”
Section: Discussionmentioning
confidence: 84%
“…21,22 Increased plasma concentration of asymmetric dimethylarginine is associated with hypertension, pulmonary hypertension, hypercholesterolemia, and severe peripheral artery occlusive diseases. 15,17,23,24 These findings suggest that asymmetric dimethylarginine is responsible for endothelial dysfunction. Barceló et al 25 assessed plasma asymmetric dimethylarginine in subjects with OSA and found it to be significantly higher in these subjects irrespective of the presence of further cardiovascular risk.…”
Section: Discussionmentioning
confidence: 84%
“…In the present study, multiple linear regression analyses were performed to control for the influence of factors other than homocysteine levels on pulmonary function. OZKAN et al [44] previously demonstrated that serum homocysteine levels were significantly higher in patients with severe sleep apnoea syndrome than in controls, suggesting that tissue hypoxia may be associated with the level of serum homocysteine. However, arterial oxygen tension and saturation were not measured in this population, and this was a limitation of our study.…”
Section: Discussionmentioning
confidence: 98%
“…20 Levels of homocysteine are mediated by endothelial injury, altered coagulation, and platelet activation. Our data show higher homocysteine levels in subjects with more severe OSA.…”
Section: Discussionmentioning
confidence: 99%